2013
DOI: 10.1371/journal.pbio.1001455
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Coordinates Ribosome Biogenesis

Abstract: The authors identify a new role of the circadian clock in coordinating mRNA translation during ribosome biogenesis, a key process for cell metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
293
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(331 citation statements)
references
References 94 publications
(109 reference statements)
32
293
4
2
Order By: Relevance
“…As anticipated, circadian clock genes show rhythms at all stages, from their respective pre-mRNAs to the accumulation of the mRNA and downstream mRNA translation (Fig. 2B), confirming that translational regulation has a minor impact upon clock gene expression (12). To assess and quantify rhythmic regulations at the different steps, we developed computational models and classified genes depending on the rhythmic or constant behavior at each measured level (pre-mRNA, mRNA, and ribosome footprints) (Dataset S1).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As anticipated, circadian clock genes show rhythms at all stages, from their respective pre-mRNAs to the accumulation of the mRNA and downstream mRNA translation (Fig. 2B), confirming that translational regulation has a minor impact upon clock gene expression (12). To assess and quantify rhythmic regulations at the different steps, we developed computational models and classified genes depending on the rhythmic or constant behavior at each measured level (pre-mRNA, mRNA, and ribosome footprints) (Dataset S1).…”
Section: Resultssupporting
confidence: 81%
“…During the last decades, efforts have been made to produce a comprehensive knowledge of the transcriptional regulation orchestrated by the circadian clock (7)(8)(9) and feeding rhythms (10,11). More recently, additional layers of regulation at the translational (12,13) and posttranslational (14) levels have been described, increasing the complexity of the phenomenon involved in the establishment of the rhythmic mRNA expression and protein synthesis landscapes.…”
mentioning
confidence: 99%
“…Although the central circadian clock, as indexed by melatonin, remained largely unaffected, the temporal organization of expression of clock genes considered to be central to circadian rhythm generation was affected in the blood transcriptome, with only NR1D2 and CSNK1E remaining rhythmic when sleeping out of phase. Histone modification, and the control of transcription and translation (4)(5)(6)(7)(8)(9), is also considered central to circadian organization of the transcriptome and the time courses of transcripts associated with all of these processes were affected in this study (Fig. 3).…”
Section: Transcripts and Associated Molecular Processes Affected By Dmentioning
confidence: 72%
“…The circadian regulation of the mammalian transcriptome includes circadian transcriptional and translational regulation by proteins such as the positive transcription factors CLOCK and ARNTL (BMAL1), and the repressors PERIOD (PER) and CRYPTOCHROME (CRY) (4), chromatin modification by factors such as E1A binding protein P300 (EP300) and the methyltransferase MLL3 (4-6), RNA polymerase activity (4,7), and posttranscriptional events such as the regulation of ribosome biogenesis and translation (8,9). Furthermore, physiological factors such as body temperature (10) and endocrine rhythms such as cortisol (11) can modify and reinforce these regulatory processes.…”
mentioning
confidence: 99%
“…15 The gene for prolactin, for example, was reported to display dynamic expression and pulsating transcription with implications for cellular differentiation. 16 Jouffe et al 17 observed rhythmic diurnal expression of many of the components required for translation initiation, indicating that the circadian clock coordinates the regulation of the biogenesis of ribosomes. The characterization of gene regulation revealed an unexpected nonlinear transcriptional program and indicates that the function of regulatory elements is complex on many time scales ranging from milliseconds to hours.…”
Section: Dynamism In Gene Expressionmentioning
confidence: 99%